A clover shaped triboelectric nanogenerator for self-powered grip strength test system. (19th September 2022) - Zhang, Xuanzi
ABSTRACT: Recently, many researchers have paid attention to triboelectric nanogenerators (TENGs) to harvest mechanical energy. Thus, a clover-shaped triboelectric nanogenerator (C-TENG) was designed to obtain mechanical vibration energy and convert them into electricity. The polytetrafluoroethylene (PTFE) film and nylon film act as the triboelectric layers, and the plastic sheet serves as the supporting structure. The maximum output power of a C-TENG can arrive at 453.75 µW. In addition, the C-TENG can play the role of a self-powered sensor for reflecting handgrip strength. This design can promote the development of TENGs in mechanical energy harvesting and self-powered human sports sensors.